Contorções do trágico na peça Dorotéia, de Nelson Rodrigues - Paulo, Juliana Ferreira de (2011)
This study tries to catch a glimpse of the tragic elements of Nelson Rodrigue's play, Dorotéia (1949), from the explanation of how its configuration recurs in the Rodriguean theather. The objective was to determine how to process this tragedy in a dramatic tradition which the configuration receives and repels, while at the same time theatricalizing the "contortions" of the tragic, which point beyond the realm of tragedy and adopt the construction of the farcical work processes of nature. Thus, the dramatic text produces two significant levels, from this theatrical "assembly", which flows into the meta-linguistic character of the play. We had as some of the analytical categories, action and characterization, and dramatic space and time. We used a theoretical basis for our research, which took into account the tragic elements considered in light of the relationship between tradition and modernity. We adopted an approach that relied on studies of Aristotle (2005), Hegel (1980), Ricoeur (1994), Szondi (2001), Rosenfeld (2008), and Luna (2005 and 2008), among others. We could observe an aesthetic option by the incorporation of processes that enable an instrumentation of the classical tradition. This option reflects a production characterized by the socio-cultural conditions of the time. Despite the complex dramatic structure, which emphasizes time and space, the tragic and farcical, and the epic drama, it remains at its end the unity of action with a slow dramatic progress made possible by the adoption of epic elements. Finally, we think that the text is constructed to culminate in the cathartic effect, while it is in reality camouflaged by a grotesque laughter and plays what we called "the tragic writhing."